Aplikace rychlostní sondy se žhavenými drátky při měření rychlostního pole za automobilovou vyústkou - Šíp, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Diplomová práce se zabývá výzkumem proudění před benchmarkovou automobilní vyústkou. Pomocí termoanemometrie bylo detailně změřeno rychlostní pole v prostoru před vyústkou a vypočtena intenzita turbulence. Byla také provedena numerická simulace proudění vzduchu z vyústky pomocí programu STAR-CCM+. Dále byl zkoumán vliv okolních ploch simulujícími reálné prostředí automobilu na proudění vzduchu z vyústky. Diplomová práce obsahuje výpočet nejistot měření. Smyslem práce je získání komplexních dat o rychlostním poli a jejich následné využití k validaci numerických simulací.

This diploma thesis deals with the research of the flow in front of the benchmark automotive vent. Using thermoanemometry, the velocity field in the area in front of the vent was measured in detail and the intensity of the turbulence was calculated. Computational fluid dynamics of the air flow from the vent was also performed using the STAR-CCM + program. In addition, the influence of the surrounding surfaces simulating the real environment of the automobile on the air flow from the vent was investigated. The diploma thesis contains the calculation of measurement uncertainty. The purpose of this thesis is to obtain complex data on the velocity field and to use them for validation of Computational fluid dynamics.
Application of an anemometric hot-wire probe to the measurement of a velocity field downstream of an automotive ventilation outlet
Keywords: Termoanemometrie; CTA; drátková sonda; rychlostní pole; automobilní vyústka; numerická simulace; Reynolds-averager Navier–Stokes; Large Eddy Simulation; Hot Wire Anemometry; CTA; wire probe; velocity field; automotive vent; Computational fluid dynamics; Reynolds-averager Navier–Stokes; Large Eddy Simulation